Electrospun composite nanofibers modified with silver nanoparticles for extraction of trace heavy metals from water and rice samples: An highly efficient and reproducible sorbent. (15th September 2023) - Amini, Shima; Kandeh, Saeed Hejabri; Ebrahimzadeh, Homeira; Khodayari, Parisa
Graphical abstract: Highlights: Electrospun nanofibers modified with AgNPs and used for extraction of heavy metals. Introduction of agar resulted in highly dispersion of AgNPs in the nanofibers. The presence of agar/AgNPs improved the sorbent extraction efficiency. The sorbent can be used for monitoring trace-level of metal ions in food samples. This method is eco-friendly due to low eluent consumption. Abstract: Herein, a composite of polyacrylonitrile (PAN)/agar/silver nanoparticles (AgNPs) electrospun nanofibers was fabricated and applied as an efficient sorbent for thin-film micro-extraction (TFME) of five metal ions followed by inductively coupled plasma optical emission spectroscopy (ICP-OES). Incorporating agar into the nanofibers followed by in situ photo-reductive reaction under UV-lamp resulted in highly uniform dispersion of AgNPs in the nanofibers. Under the optimized conditions, agreeable linearity was acquired in the range of 0.5–250.0 ng mL −1 (R 2  ≥ 0.9985). The LODs (based on S/N = 3) were attained in the range of 0.2 to 0.5 ng mL −1 . The relative standard deviations (RSDs) were between 4.5% and 5.6% (intra-day, n = 5) and 5.3%–5.9% (inter-day, n = 3) for three sequential days. The developed method was investigated with water and rice samples, and recoveries (93.9–98.0%) indicated that the PAN/agar/AgNPs could be a promising film for the adsorption of heavy metal ions in varied samples.